Mixed-Lineage kinase 3 delivers CD3/CD28-derived signals into the IκB kinase complex - Hehner, Steffen Peter; Hofmann, Thomas G.; Dröge, Wulf (Molecular and cellular biology, 2000)
The phosphorylation of IκB by the multiprotein IκB kinase complex (IKC) precedes the activation of transcription factor NF-κB, a key regulator of the inflammatory response. Here we identified the mixed-lineage group kinase 3 (MLK3) as an activator of NF-κB. Expression of the wild-type form of this mitogen-activated protein kinase kinase kinase (MAPKKK) induced nuclear immigration, DNA binding, and transcriptional activity of NF-κB. MLK3 directly phosphorylated and thus activated IκB kinase alpha (IKKα) and IKKβ, revealing its function as an IκB kinase kinase (IKKK). MLK3 cooperated with the other two IKKKs, MEKK1 and NF-κB-inducing kinase, in the induction of IKK activity. MLK3 bound to components of the IKC in vivo. This protein-protein interaction was dependent on the central leucine zipper region of MLK3. A kinase-deficient version of MLK3 strongly impaired NF-κB-dependent transcription induced by T-cell costimulation but not in response to tumor necrosis factor alpha or interleukin-1. Accordingly, endogenous MLK3 was phosphorylated and activated by T-cell costimulation but not by treatment of cells with tumor necrosis factor alpha or interleukin-1. A dominant negative version of MLK3 inhibited NF-κB- and CD28RE/AP-dependent transcription elicited by the Rho family GTPases Rac and Cdc42, thereby providing a novel link between these GTPases and the IKC.
Gesehen am 03.02.2021